Avaliação de contaminantes inorgânicos e orgânicos em álcool combustível utilizando eletroforese capilar - Pereira, Elisabete A.; Tavares, Marina F.M.; Stevanato, Alessandra [UNESP]; Cardoso, Arnaldo A. [UNESP] (Elsevier, 2006)
This work reports the analysis of inorganic and organic contaminants in alcohol fuel samples using capillary electrophoresis. Chloride and sulfate were analyzed in nitrate/ monochloroacetic acid at 10 mmol L -1 concentration each under indirect UV detection (210 nm). The analysis of aldehydes is based on the 216 nm detection of 3-methyl-2-benzothiazoline hydrazone adducts. The running buffer consisted of 20 mmol L -1 tetraborate, 40 mmol L -1 sodium dodecyl sufate and 12 mmol L-1 β-ciclodextrin. Both methodologies were applied to real samples indicating inorganic ion concentrations from 0.15 to 6.64 mg kg -1 and aldehydes from 32.0 to 91.3 mg L -1.
Evaluation of inorganic and organic contaminants in alcohol fuel by capillary electrophoresis
Keywords: Alcohol fuel; Capillary electrophoresis; Inorganic and organic contaminants